2014
DOI: 10.1080/03650340.2014.978302
|View full text |Cite
|
Sign up to set email alerts
|

Tillage effects on soil properties and maize productivity in western Turkey

Abstract: Information regarding the evaluation of long-term tillage effects on soil properties and summer maize growth after winter vetch in western Turkey is not available. Therefore, this study was conducted for 5 years with three types of tillage including conventional (mouldboard plough) and conservation (rototiller and chisel). Results indicated that tillage had no significant effect on penetration resistance, except at the bottom of 20 cm soil depth where it was higher in mouldboard plough than in rototiller and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 23 publications
0
11
2
Order By: Relevance
“…These results are not in agreement with other studies that differences in K due to a more rapid mineralization when chisel had slower mineralization (Hussain et al, 1999). Lipiec and Stepniewski (1995) and Hussain et al (1999) reported that K generally decreases with increasing soil compaction when compaction was occurred under CT topsoil of this study area (Ozpinar and Ozpinar, 2014). S and N were higher in both aboveground and roots in all tillage systems (Figure 2 The cited authors found that higher Mn in roots of reduced tillage when compared with plough.…”
Section: Accepted Manuscriptcontrasting
confidence: 59%
See 4 more Smart Citations
“…These results are not in agreement with other studies that differences in K due to a more rapid mineralization when chisel had slower mineralization (Hussain et al, 1999). Lipiec and Stepniewski (1995) and Hussain et al (1999) reported that K generally decreases with increasing soil compaction when compaction was occurred under CT topsoil of this study area (Ozpinar and Ozpinar, 2014). S and N were higher in both aboveground and roots in all tillage systems (Figure 2 The cited authors found that higher Mn in roots of reduced tillage when compared with plough.…”
Section: Accepted Manuscriptcontrasting
confidence: 59%
“…(Ozpinar and Ozpinar, 2014). Some authors found higher Fe in reduced tillage than plough (Houx et al, 2011;García-Marco et al, 2014), while other authors observed the opposite tendency (Lavado et al, 1999).…”
Section: Accepted Manuscriptmentioning
confidence: 89%
See 3 more Smart Citations